Analysis of Physical and Mechanical Properties of Andesite Lava Geulis Mountain Area, Jatinangor, West Java - Abdullah, Fajar; Sophian, Raden Irvan; Khoirullah, Nur; Zakaria, Zufialdi; Asykarulloh, Abdul Wahid; Taufiq, Mochamad Muslim; Shafira, Nisa; Putri, Revena Denia (Journal of Geological Sciences and Applied Geology, 2021)
Jatinangor is an area composed of material from volcanic activity, one of the results of volcanic activity is andesite rock. The purpose of this research is to provide information related to the physical and mechanical properties of the lava rock in the Gunung Geulis area so that if there is construction work or rock utilization there is already information about the characteristics of the rock. The method used in this study is a laboratory experiment by conducting tests on 9 selected rock samples. The results of laboratory testing can be concluded the rock in the research area is andesite rocks and have rock physical properties namely Natural density (1.5 – 1.6 gr/cc), Saturated density (1.6 – 1.7 g/cc), Dry Density (1.5 – 1.6 g/cc), Bulk Saturated Surface Dry (SSD) Specific Gravity (2.3 – 2.4), Apparent Specific Gravity (2.5 – 2.7), absorption (3 – 5.9%), Natural moisture content (0.6 – 2.3%),  Porosity (4.9 – 9.4%) and the mechanical properties of the rock, namely the compressive strength of the rock, ranged from 33,099 – 85,096 Mpa. Based on the results and analysis, the mechanical properties of rocks, namely the compressive strength of rocks in the study area, have varying values and varied physical properties of rocks. Physical and mechanical properties of rocks that are correlated based on linear correlation are the compressive strength of rocks with absorption, Natural moisture content, and porosity. These parameters will show the relationship that can affect the compressive strength of rocks. So that when using rock in construction work, mining, the use of rock needs to pay attention to the compressive strength or mechanical properties and physical properties of the rock.